Purification of bioactive phenolics from Phanerochaete chysosporium biomass extract on selected macroporous resins - Idris, Zulkarnain Mohamed; Mohamed Dzahir, Mohd Irfan Hatim; Jamal, Parveen; Ahmad Barkat, Anumsima; Xian, R. L.W. (IOP Publishing, 2017)
In this study, two different types of macroporous resins known as XAD-7HP and HP-20 were evaluated for the adsorption and desorption properties against bioactive phenolics extracted from Phanerochaete chrysosporium. For static sorption, the study were conducted at different phase contact time, solution pH and ethanol concentration by static adsorption/ desorption method. From the results, it was found that the adsorption capacity for both resins had has no significant difference. Then, the kinetic adsorption data were analyzed with both pseudo-first-order and pseudo-second-order equations and the later performed better. The adsorption isotherm data were fitted well by both Langmuir and Freundlich models. Meanwhile in desorption study, HP-20 and XAD-7HP gave 90.52% and 88.28% recoveries, respectively. Considering the desorption results of the macroporous resins, HP-20 and XAD-7HP were packed in chromatography column to further purify the phenolics. For dynamic adsorption, breakthrough capacity of HP-20 (0.522) was found to be higher than XAD7HP (0.131). Different ethanol concentrations (30% to 50% (v/v)) were investigated at fixed flowrate (1 ml/min) on phenolics recovery from both types of resins. The highest recovery of bioactive phenolics was 94.3% using XAD-7HP resins at 50% (v/v) of ethanol. Only 77.1% of bioactive phenolics were recovered using HP-20 resin at the same experimental conditions. The purified extract subsequently was analyzed using HPLC. The results showed that three phenolics (gallic acid 3,4-dihydroxybenzoic acid and 4-hydroxybenzoic acid) were identified with higher concentrations as compared to non-purified extract. Finally, the purified extract was tested for scavenging activity against DPPH, and it showed that the activity increased significantly to 90.80% from 59.94% in non-purified extract.